Keabsahan Surat Keterangan Lahir dalam Pemberian Identitas Anak (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Currently, there are many cases of unclear child identity status, such as for adopted children. The importance of a birth certificate issued immediately after delivery is to provide the authentic identity details of the child, which are vital for establishing the child’s origin. Some key points regarding adopted children are that adoption does not sever the biological relationship between the child and their birth parents. An adopted child has the same rights as a biological child, such as having a birth certificate and being included in the Family Card. However, an adopted child does not inherit from their adoptive parents unless specified by a will or a mandatory will. Medical personnel are required to issue a birth certificate that reflects the actual circumstances, as this will impact the child's rights in the future. A birth certificate contains information such as the date, time, and place of birth, gender, weight, and the names of the parents. According to Law No. 35 of 2014, Article (1), an individual's identity must be established at birth, and Article (2) states that the identity is documented in a birth certificate. The state, government, society, family, and parents are all obligated to ensure the protection of children, as they are physically and psychologically vulnerable, immature, and still in need of protection.